Development of novel bacterial consortium for biodegradation of paraffin wax in crude oil - Adlan Mustafa, Nur Aina (2020)
The deposition of paraffin wax in crude oil is a problem faced by the oil and gas industry during the extraction, transportation, and refining of crude oil. Millions of dollars were spent annually to control wax deposition in the pipeline. As an alternative to prevent wax deposition, this study aimed to develop a novel bacterial consortium for the biodegradation of paraffin wax in crude oil. Eleven paraffin wax degrading bacteria were screened at 70 °C using crude oil B and these isolates showed the ability to degrade the crude oil. The medium for bacterial growth and degradation was optimized with yeast extract alone to enhance the biodegradation of crude oil. The 16S rRNA gene identification of isolates revealed that these isolates are Geobacillus kaustophilus strain N3A7, Geobacillus kaustophilus strain NFA23, Geobacillus kaustophilus strain DFY1, Parageobacillus caldoxylosilyticus strain DFY3, Parageobacillus caldoxylosilyticus strain AZ72, Geobacillus jurassicus strain MK7, Anoxybacillus geothermalis strain D9 (previously identified), Geobacillus thermocatenulatus strain T7, Geobacillus stearothermophilus strain SA36, Geobacillus stearothermophilus strain AD24, and Geobacillus stearothermophilus strain AD11. Gas chromatography-mass spectrometry (GCMS) analysis of residual hydrocarbon showed more than 70% biodegradation efficiency by strains AD11, DFY1, AD24, N3A7, and MK7 compared to other strains. The degradative alkane monooxygenase enzyme activity of strain AD24 was the highest. Strains N3A7, MK7, DFY1, AD11, and AD24 (high degraders) also demonstrated relatively higher alcohol dehydrogenase, lipase, and esterase activity compared to other strains. Five consortia were developed based on the biodegradation efficiency of 11 bacterial strains. Consortium 3 (77.8%) showed the highest biodegradation with more long-chain alkane degraded throughout the incubation compared to other consortia. The degradation of long-chain alkane (paraffin wax) by all consortia also caused an increase of short-chain alkanes contents. Consortium 3 also exhibited higher alkane monooxygenase, alcohol dehydrogenase, lipase, and esterase activity compared to other consortia. The dominant bacteria in the consortia were identified by denaturing gradient gel electrophoresis (DGGE). The results showed that P. caldoxylosilyticus strain DFY3, P. caldoxylosilyticus strain AZ72, and G. kaustophilus strain N3A7 were dominant in consortium 1, consortium 2, and consortium 3, respectively throughout the incubation. In consortium 4, P. caldoxylosilyticus strain DFY3, G. thermocatenulatus strain T7, and G. stearothermophilus strain SA36 were dominant on different days of incubation. Consortium 5 also showed the dominance of G. kaustophilus sp. and G. stearothermophilus sp. on different days of incubation. In conclusion, the bacterial consortia showed improvement in degrading more long-chain hydrocarbons while increasing some short-chain hydrocarbons. This improvement could lower oil viscosity and reduce oil production loss